A look at the global educational crisis through the lens of experience of the history of science. Part II. The structure of general education content - V. L. Gapontsev; V. A. Fedorov; Ye. M. Dorozhkin (Russian State Vocational Pedagogical University, 2021)
Introduction. The first part of this work is devoted to the examination of the scientific knowledge structure as a three-level scheme of its division (the field of phenomena of nature, laws of nature and the field of symmetry principles), wherein each next level provides the previous one with its structure. According to V. S. Lednev's approach, scientific knowledge is a determinant of the general education content. Therefore, the general education content structure requires to be revised as well. Aim. The aim of the current study is the determination of a needed alteration of the general education structure corresponding to integrative trends, which have been registered in the process of formation of the scientific knowledge new structure.Methodology and research methods. The methodology of the study is based on the ideology of F. Klein (the Erlangen programme) and the ideas of E. Wigner about the levels of division of the scientific knowledge field (the totality of these ideas allows using them as a tool for description of the scientific knowledge structure and, consequently, of the structure of the education content, the determinant whereof it is); on the personal-activity approach developed by V. S. Lednev for the analysis of the structure of the education content, and on the approaches to description of the behaviour of complex systems on the base of regular laws established by synergetics.Results and scientific novelty. A new element, specifically "Structure of scientific knowledge (symmetry)" through line, is proposed for introducing into the general education content structure. Its function is the global integration of subject-based through lines of the general education. On this basis, it is possible to optimise the content of education that balances the process of differentiation within scientific knowledge. It allows solving one of the topical issues of the global educational crisis related to the constant growth of the scientific knowledge volume and fragmentation thereof. The present paper takes into consideration that certain features of sporadic formation of such a new element of the education content structure take place. Among them, one can mention the attempts to launch "Concepts of the Modern Natural Science" and "Scientific World View" courses, discussion of possibilities to use synergetics in pedagogy and active discussion of use of the ideas of symmetry within various disciplines - from humanitarian to science, technology, engineering and mathematics (STEM). The perspectives of further development of formulated ideas about the scientific knowledge structure and the general education content structure in light of trends in STEM are also discussed.Practical significance. The ideas about "Structure of scientific knowledge (symmetry)" through line will be utilised for task-oriented revision and re-distributing of the content of subject-based through lines of the general education with the aim of its optimisation, taking into account the highest level of the scientific knowledge integration, which was formed in the course of the evolution thereof.